Surviving Strategy of Hospitality Sector in Pandemic Situation - Ardani, Edvi Gracia; Harianto, Anton (E-Journal of Tourism; Volume 8 Number 1 (March 2021), 2021)
Crisis in 2020 is the impact of unexpected Covid-19 spreading all around the world in which period all social and economic aspects are forced to slowing down or even temporarily stopped. In almost all countries in the world, only few sectors are allowed to run the business normally. The sectors are mainly business offering basic needs such as grocery stores, certain food and beverage, and medical. The phenomena attack blatantly hospitality sectors and it must be faced by the stakeholders of the industry. In Indonesia, hospitality industry does suffer. The human centric characteristic of the industry requires interactions between people. Human interactions are well explained as the core activities in tourism industry in the old normal while it is to be avoided during the new normal of Covid-19. Business owners and managers fight against the condition which finally pushed them hardly to unfortunate decisions for the human capital of the industry and for many other strategic issues. The crisis is present and brings a huge impact to the hospitality sector that includes hotel and restaurant business. This study is to describe the picture of how this sector in Jakarta area overcomes the pandemic situation and until what extent the management is capable to handle. A qualitative research is conducted with narrative approach, by empathising to the human capital in the sector using grounded theory approach. Challenges are encountered by the hospitality practitioners and each one of them are trying to survive with their own way.